SUNSCEEN FOR TRAVELLERS - Lavi N, Novita (E-Jurnal Medika Udayana; vol 2 no6(2013):e-jurnal medika udayana, 2013)
The sun exposure brings negative effects on the skin such like early aging, spots and skin cancer as the most terrible effect. To reduce the adverse effects of the sun, it is not enough just to behavioral therapy, but also had no protection from the outside. Especially for travellers that exposed by the sun excessively. There is sunscreen, product specially formulated to absorb or deflect ultraviolet rays. A sunscreen preparation contains chemical compounds that can absorb, scatter or reflect sunlight on the skin. This writing contains about effect of ultraviolet, skin protection from ultraviolet from behavioral aspect, variaty and contents of sunscreen and sunscreen application for travellers. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Skin Cancer, Sunscreen, Sun, Ultraviolet